Nitrogen-doped waste biomass porous carbon / cellulose composite gel material and preparation method thereof
Through the preparation of nitrogen-doped waste biomass porous carbon and cellulose composite gel materials, the problem of agricultural and forestry waste utilization is solved, efficient resource conversion and pollutant removal solutions are provided, and efficient environmental restoration and catalytic performance are achieved.
Patent Information
- Application Number
- CN202411434857.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to effectively utilize agricultural and forestry waste, resulting in environmental pollution and waste of resources. Traditional porous charcoal is non-renewable and lacks efficient alternative materials.
Using nitrogen-doped waste biomass porous carbon and cellulose composite gel material, the waste biomass is mixed and heated with nitrogen-containing organic matter, followed by treatment with activator and ionic liquid, and finally combined with cellulose to form a high-quality Composite gel with specific surface area and excellent mechanical properties.
It realizes efficient resource utilization and provides materials with excellent mechanical properties, conductivity and catalytic properties. It is suitable for environmental restoration, catalysis and energy storage fields, improving pollutant removal efficiency and material recycling rate.
Smart Images

Figure CN119281391A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a nitrogen-doped waste biomass porous carbon / cellulose composite gel material, belongs to the field of new material science, and is applied to the fields of environmental functional materials, catalysis, energy storage, etc. Background Art
[0002] As a major agricultural country, my country produces about 1.35 billion tons of agricultural and forestry wastes such as bagasse every year. However, the lack of large-scale high-value utilization technology has led to open-air burning, which has caused environmental pollution and waste of resources. Therefore, it is urgent to develop an effective technology that can strengthen the management and restoration of rural land pollution and improve the resource utilization of agricultural and forestry wastes.
[0003] Traditional porous carbon mainly comes from fossil fuels and is a non-renewable resource. However, agricultural and forestry wastes are widely available, low-cost and renewable. Preparing agricultural and forestry wastes into biomass porous carbon can not only effectively replace traditional porous carbon, but more importantly, waste biomass porous carbon has a larger specific surface area, higher porosity, better electrical conductivity and excellent scalability, which has attracted widespread attention in the fields of environmental functional materials, catalysis, energy storage, etc.
[0004] Cellulose is a natural, abundant, renewable, green polymer. Due to its unique asymmetric chemical structure, cellulose has excellent mechanical strength and flexibility. If cellulose is composited with nitrogen-doped waste biomass porous carbon, the nitrogen-doped waste biomass porous carbon can be embedded in cellulose, which is conducive to higher utilization and better hydrophilicity. At the same time, a composite gel material with a certain specific surface area, strong mechanical properties and excellent hydrophilicity is obtained, which is more conducive to recycling and reuse. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a nitrogen-doped waste biomass porous carbon cellulose composite gel material, which is characterized by comprising the following steps:
[0006] S1: Mix waste biomass and nitrogen-containing organic matter in a certain proportion, place the mixture in a tubular furnace protected by inert gas, heat it to a specified temperature T1, and keep it warm for a certain period of time to obtain nitrogen-doped waste biochar;
[0007] S2: After the nitrogen-doped biochar and the activator are mixed in a certain proportion, the mixture is placed in a tubular furnace protected by inert gas, heated to a specified temperature T2, and kept warm for a certain period of time, the activated mixture is rinsed with hydrochloric acid and deionized water, and vacuum dried to obtain nitrogen-doped waste biomass porous carbon with a high specific surface area;
[0008] S3: After the ionic liquid is heated to a specified temperature T3, 1 wt% to 6 wt% of cellulose is added under constant temperature conditions, and a cellulose ionic liquid solution of a certain concentration is obtained after stirring and dissolving;
[0009] S4: after lowering the temperature of the cellulose ionic liquid to a specified temperature T4, adding nitrogen-doped waste biomass porous carbon at a constant temperature, stirring and ultrasonically dispersing, to obtain a mixed solution of nitrogen-doped waste biomass porous carbon and cellulose ionic liquid of a certain concentration;
[0010] S5: degassing the final mixed solution, regenerating it with a coagulation solution, washing it, and drying it to obtain a nitrogen-doped waste biomass porous carbon-cellulose composite gel.
[0011] In the present invention, the waste biomass includes sugarcane bagasse, corn stalks, kapok fibers, ganoderma lucidum residues and other agricultural and forestry wastes.
[0012] In the present invention, the nitrogen-containing organic matter includes urea, melamine and ethylenediamine.
[0013] In the present invention, the activator is potassium hydroxide, sodium hydroxide, potassium carbonate, and zinc chloride.
[0014] In the present invention, the ionic liquid is selected from imidazolium salt ionic liquids, pyridinium salt ionic liquids, novel choline and non-imidazole salt ionic liquids.
[0015] In the method of the present invention, in step S1, the mass ratio of the waste biomass to the nitrogen-containing organic matter is 1:0.5-2, and the flow rate of the inert gas is 30-100 ml min -1 The heating rate is 3~10℃ min -1 , temperature T1 is 200~400℃, and insulation time is 0.5~3 hours.
[0016] In the method of the present invention, in step S2, the mass ratio of nitrogen-doped biochar to activator is 1:0.25-3, and the flow rate of inert gas is 30-100 ml min -1 , 3~10℃ min -1 , temperature T2 is 600-800°C, insulation time is 0.5-3 hours, hydrochloric acid concentration is 0.5-2M, and vacuum drying is performed at 60-80°C.
[0017] In the method of the present invention, in step S3, the temperature T3 is 80-110°C.
[0018] The method of the present invention, in step S4, the temperature T4 is 50-95°C, the mass ratio of nitrogen-doped waste biomass porous carbon and cellulose is 0.1%-50%, the mixing temperature is 60-80°C, the stirring speed is 300-500rpm, the stirring time is 10-30 minutes, and the ultrasonic time is 10-30 minutes.
[0019] In the method described in the present invention, in step S5, the coagulation liquid is deionized water, methanol, or ethanol, and the drying step is freeze drying, supercritical CO2 drying, or 60°C vacuum drying.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are: the present invention provides a nitrogen-doped waste biomass porous carbon cellulose composite gel material and a preparation method thereof, which has better mechanical properties than traditional porous carbon and is conducive to recycling and reuse; compared with cellulose gel, it has better conductivity and catalytic properties, and as an environmental functional material or catalytic material, it has excellent pollutant removal efficiency and catalytic activity.
[0021] The nitrogen-doped waste biomass porous carbon cellulose composite gel material is easy to prepare and can turn waste biomass into treasure. In addition to being used in the field of environmental remediation, it can also be used in the fields of energy storage and microwave absorption.
[0022] Waste biomass is widely available and cheap. Recycling waste biomass is one of the important ways to achieve sustainable development. Nitrogen-doped waste biomass porous carbon has rich pore structures and surface groups, which can effectively promote the activation of persulfate and the oxidative degradation of organic pollutants. In addition, the carbon material itself is green and non-toxic, which can effectively avoid secondary pollution to the environment caused by ion leaching.
[0023] Using cellulose gel as a carrier makes the catalyst have higher utilization rate and better hydrophilicity, increases the effective contact of reactants, and improves degradation efficiency. The present invention uses waste biomass as raw material and cellulose gel as a carrier to prepare a nitrogen-doped waste biomass porous carbon composite gel material with a large specific surface area, active sites and good hydrophilicity, which can not only effectively activate persulfate to produce active species, but also facilitate recycling and reuse, while enhancing the adsorption capacity of pollutants, thereby improving the removal efficiency of pollutants.
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In the following examples, waste biomass bagasse was obtained from Guangxi Yuante Agricultural Technology Co., Ltd., urea, potassium carbonate, and melamine were provided by Aladdin Reagent Co., Ltd., 36% hydrochloric acid reagent was provided by Guangzhou Chemical Reagent Factory, and ionic liquid was purchased from Shanghai Chengjie Chemical Co., Ltd. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the SEM image of the nitrogen-doped bagasse cellulose composite gel material prepared in Example 1.
[0027] Figure 2 This is the columnar nitrogen-doped bagasse cellulose composite gel prepared in Example 1. DETAILED DESCRIPTION
[0028] In order to better understand the content of the present invention, the present invention is further described below in conjunction with examples and drawings, but the implementation of the present invention is not limited thereto, and the scope of protection claimed by the present invention is not limited to the scope represented by the examples. In the present invention, Figure 1 This is the SEM image of the nitrogen-doped bagasse cellulose composite gel material prepared in Example 1. Figure 2 This is the columnar nitrogen-doped bagasse cellulose composite gel prepared in Example 1.
[0029] Example 1
[0030] S1: Bagasse and urea were mixed thoroughly in a mass ratio of 1:1, and then the mixture was placed in an argon-protected tubular furnace for high-temperature carbonization. The flow rate of argon was 30 ml min -1 The heating rate of the tube furnace is 5℃ min -1 , the carbonization temperature is 300℃ and the holding time is 1 hour.
[0031] S2: The carbonized sample was mixed with potassium carbonate at a mass ratio of 1:2. The sample was placed in a tube furnace for high-temperature activation under an argon atmosphere at a flow rate of 30 ml min -1 The heating rate of the tube furnace is 3℃ min -1 The carbonization temperature was 750℃ and the holding time was 1.5 hours. The activated sample was rinsed with 1M hydrochloric acid and deionized water until pH = 7 and vacuum dried at 80℃ to obtain nitrogen-doped bagasse porous carbon with high specific surface area.
[0032] S3: Add cellulose to the ionic liquid (the mass ratio of microcrystalline cellulose to 1-butyl-3-methylimidazolium chloride is 5:95), mix and heat to 95° C. and stir for 4 hours under a nitrogen atmosphere until the cellulose is completely dissolved in the ionic liquid to obtain a cellulose ionic liquid.
[0033] S4: After the temperature of the cellulose ionic liquid is lowered to 70°C, nitrogen-doped bagasse porous carbon (the mass ratio of nitrogen-doped bagasse porous carbon to cellulose is 1:1) is added at a constant temperature, stirred for 10 minutes and then ultrasonicated for 30 minutes to obtain a mixture of nitrogen-doped waste biomass porous carbon and 5 cellulose ionic liquid;
[0034] S5: The final mixed solution was transferred to a beaker for degassing, and then the mixture was immersed in ethanol for regeneration to obtain a columnar nitrogen-doped bagasse cellulose composite gel, which was repeatedly washed with deionized water until 0.1 mol mL -1 The AgNO3 solution was added to the soaking liquid until no precipitation was detected. The columnar nitrogen-doped bagasse cellulose composite gel was obtained by freeze drying.
[0035] Example 2
[0036] S1: Bagasse and urea were mixed thoroughly at a mass ratio of 2:1, and then the mixture was placed in an argon-protected tubular furnace for high-temperature carbonization. The argon flow rate was 30 ml min -1 The heating rate of the tube furnace is 5℃ min -1 , the carbonization temperature is 350℃ and the holding time is 1 hour.
[0037] S2: The carbonized sample was mixed with potassium carbonate at a mass ratio of 1:3. The sample was placed in a tube furnace for high-temperature activation under an argon atmosphere at a flow rate of 30 ml min -1 The heating rate of the tube furnace is 3℃ min -1 The carbonization temperature was 800°C and the holding time was 1.5 hours. The activated sample was rinsed with 1M hydrochloric acid and deionized water until pH = 7 and vacuum dried at 80°C to obtain nitrogen-doped bagasse porous carbon with high specific surface area.
[0038] S3: Add cellulose to the ionic liquid (the mass ratio of microcrystalline cellulose to 1-butyl-3-methylimidazolium chloride is 5:95), mix and heat to 95° C. and stir for 4 hours under a nitrogen atmosphere until the cellulose is completely dissolved in the ionic liquid to obtain a cellulose ionic liquid.
[0039] S4: After the temperature of the cellulose ionic liquid is lowered to 70°C, nitrogen-doped bagasse porous carbon (the mass ratio of nitrogen-doped bagasse porous carbon to cellulose is 1:1) is added at a constant temperature, stirred for 10 minutes and then ultrasonicated for 30 minutes to obtain a mixture of nitrogen-doped waste biomass porous carbon and 5 cellulose ionic liquid;
[0040] S5: The final mixed solution was transferred to a beaker for degassing, and then the mixture was immersed in ethanol for regeneration to obtain a columnar nitrogen-doped bagasse cellulose composite gel, which was repeatedly washed with deionized water until 0.1 mol mL-1 The AgNO3 solution was added to the soaking liquid until no precipitation was detected. The columnar nitrogen-doped bagasse cellulose composite gel was obtained by freeze drying.
[0041] Example 3
[0042] S1: Bagasse and urea were mixed thoroughly in a mass ratio of 1:1, and then the mixture was placed in an argon-protected tubular furnace for high-temperature carbonization. The flow rate of argon was 100 ml min -1 The heating rate of the tube furnace is 10℃ min -1 , the carbonization temperature is 200℃ and the holding time is 0.5 hour.
[0043] S2: The carbonized sample was mixed with potassium carbonate at a mass ratio of 4:1. The sample was placed in a tube furnace for high-temperature activation under an argon atmosphere. The flow rate of argon was 100 ml min -1 The heating rate of the tube furnace is 10℃ min -1 The carbonization temperature was 600°C and the holding time was 0.5 hours. The activated sample was rinsed with 0.5M hydrochloric acid and deionized water until pH = 7 and vacuum dried at 60°C to obtain nitrogen-doped bagasse porous carbon with high specific surface area.
[0044] S3: Add cellulose to the ionic liquid (the mass ratio of microcrystalline cellulose to 1-butyl-3-methylimidazolium chloride is 5:95), mix and heat to 80° C. and stir for 4 hours under a nitrogen atmosphere until the cellulose is completely dissolved in the ionic liquid to obtain a cellulose ionic liquid.
[0045] S4: After the temperature of the cellulose ionic liquid is lowered to 50°C, nitrogen-doped bagasse porous carbon (the mass ratio of nitrogen-doped bagasse porous carbon to cellulose is 1:1) is added at a constant temperature, stirred for 10 minutes and then ultrasonicated for 30 minutes to obtain a mixture of nitrogen-doped waste biomass porous carbon and cellulose ionic liquid;
[0046] S5: The final mixed solution was transferred to a beaker for degassing, and then the mixture was immersed in deionized water for regeneration to obtain a columnar nitrogen-doped bagasse cellulose composite gel, which was repeatedly washed with deionized water until 0.1 mol mL -1 The AgNO3 solution was added to the soaking liquid until no precipitation was detected. The columnar nitrogen-doped bagasse cellulose composite gel was obtained by freeze drying.
[0047] Comparative Example 1
[0048] Except that urea was not added, the rest was prepared according to the same steps as in Example 1.
[0049] Comparative Example 2
[0050] Except that no carbonic acid was added, the rest was prepared by the same steps as in Example 1.
[0051] The steps are the same as in Example 1;
[0052] Comparative Example 3
[0053] Except that potassium carbonate is replaced by potassium hydroxide in step S2, the rest is prepared by the same steps as in Example 1.
[0054] Comparative Example 4
[0055] Steps S1-S2 are the same as those in Example 1; the subsequent steps are no longer performed.
[0056] Experimental Example: The experiment of removing organic pollutants from pharmaceuticals and personal care products by activated persulfate advanced oxidation technology was placed in a 100 mL beaker for 2 hours. The reaction solution was 100 mL, and the concentration of organic pollutants from pharmaceuticals and personal care products was 20 mg L -1 , 100mg L -1 Nitrogen-doped bagasse porous carbon-cellulose composite gel (or 50 mg L -1 Nitrogen-doped bagasse porous carbon) and 1 mM peroxymonosulfate. During the reaction, the magnetic stirrer speed was 200 rpm min -1 , the solution temperature was 25°C. During the reaction, about 1 mL of the solution was sampled regularly and filtered through a 0.45 μm polytetrafluoroethylene membrane. High performance liquid chromatography (HPLC) was used to quantitatively analyze the target pollutants to investigate the removal efficiency of the waste biomass porous carbon gel on the target pollutants.
[0057] The target pollutants are tetracycline hydrochloride, carbamazepine and capecitabine.
[0058]
Claims
1. A method for preparing nitrogen-doped waste biomass porous carbon / cellulose composite gel material, characterized in that: The following steps are involved: S1: Mix waste biomass and nitrogen-containing organic matter in a certain proportion, place the mixture in a tubular furnace protected by inert gas, heat it to a specified temperature T1, and keep it warm for a certain period of time to obtain nitrogen-doped waste biochar; S2: After the nitrogen-doped biochar and the activator are mixed in a certain proportion, the mixture is placed in a tubular furnace protected by inert gas, heated to a specified temperature T2, and kept warm for a certain period of time, the activated mixture is rinsed with hydrochloric acid and deionized water, and vacuum dried to obtain nitrogen-doped waste biomass porous carbon with a high specific surface area; S3: After the ionic liquid is heated to a specified temperature T3, 1 wt% to 6 wt% of cellulose is added under constant temperature conditions, and a cellulose ionic liquid solution of a certain concentration is obtained after stirring and dissolving; S4: after lowering the temperature of the cellulose ionic liquid to a specified temperature T4, adding nitrogen-doped waste biomass porous carbon at a constant temperature, stirring and ultrasonically dispersing, to obtain a mixed solution of nitrogen-doped waste biomass porous carbon and cellulose ionic liquid of a certain concentration; S5: degassing the final mixed solution, regenerating it with a coagulation solution, washing it, and drying it to obtain a nitrogen-doped waste biomass porous carbon-cellulose composite gel.
2. The method for preparing a nitrogen-doped waste biomass porous carbon cellulose gel composite catalytic material according to claim 1, characterized in that: The waste biomass includes sugarcane bagasse, corn stalks, kapok fibers, ganoderma lucidum residues and other agricultural and forestry wastes.
3. The method for preparing a nitrogen-doped waste biomass porous carbon / cellulose composite gel material according to claim 1, characterized in that: The nitrogen-containing organic matter includes urea, melamine and ethylenediamine.
4. The method for preparing a nitrogen-doped waste biomass porous carbon / cellulose gel composite material according to claim 1, characterized in that: The activator is potassium hydroxide, sodium hydroxide, potassium carbonate and zinc chloride.
5. The method for preparing a nitrogen-doped waste biomass porous carbon / cellulose gel composite material according to claim 1, characterized in that: The ionic liquid is selected from imidazolium salt ionic liquids, pyridinium salt ionic liquids, novel choline ionic liquids and non-imidazole salt ionic liquids.
6. The method for preparing a nitrogen-doped waste biomass porous carbon / cellulose gel composite material according to claim 1, characterized in that: In step S1, the mass ratio of the waste biomass to the nitrogen-containing organic matter is 1:0.5-2, and the flow rate of the inert gas is 30-100 ml min -1 The heating rate is 3~10℃min -1 , temperature T1 is 200~400℃, and insulation time is 0.5~3 hours.
7. The method for preparing a nitrogen-doped waste biomass porous carbon / cellulose gel composite material according to claim 1, characterized in that: In step S2, the mass ratio of nitrogen-doped biochar to activator is 1:0.25-3, and the flow rate of inert gas is 30-100 ml min -1 , 3~10℃min -1 , temperature T2 is 600-800°C, insulation time is 0.5-3 hours, hydrochloric acid concentration is 0.5-2M, and vacuum drying is performed at 60-80°C.
8. The method for preparing a nitrogen-doped waste biomass porous carbon-cellulose gel composite material according to claim 1, characterized in that: In step S3, the temperature T3 is 80-110°C.
9. The method for preparing a nitrogen-doped waste biomass porous carbon / cellulose gel composite material according to claim 1, characterized in that: In step S4, the temperature T4 is 50-95°C, the mass ratio of nitrogen-doped waste biomass porous carbon / cellulose is 0.1%-50%, the mixing temperature is 60-80°C, the stirring speed is 300-500rpm, the stirring time is 10-30 minutes, and the ultrasonic time is 10-30 minutes.
10. The method for preparing a nitrogen-doped waste biomass porous carbon / cellulose gel composite material according to claim 1, characterized in that: In step S5, the coagulation liquid is deionized water, methanol, or ethanol, and the drying step is freeze drying, supercritical CO2 drying, or 60°C vacuum drying.
11. The nitrogen-doped waste biomass porous carbon / cellulose composite gel material prepared according to the method for preparing a nitrogen-doped waste biomass porous carbon / cellulose gel composite material according to any one of claims 1 to 10.
Citation Information
Cited By
Preparation process of modifier-doped iron-containing magnetic biochar and method for adsorbing organic pollutants by using modifier-doped iron-containing magnetic biochar
CN120054444A